Políticas públicas e agricultura familiar : um estudo sobre o Pronaf nos municípios de Panambi e Passo Fundo (RS), 1995-2020 - Lopes, Indaia Dias (2022)
The National Program for Strengthening Family Agriculture (Pronaf) is undoubtedly one of the great public policies of recent decades in Brazil. This Program was created in 1995, in a context of intense mobilization of representative movements of family farming. This thesis aims to analyze Pronaf execution in the municipalities of Panambi and Passo Fundo (RS), from 1995 to 2020, seeking to identify the main social actors involved in the articulation of public policy at the local level and their perceptions about the contributions and Program limitations. Priority is given to the local space with the study of two cases, Panambi and Passo Fundo, for considering them with different elements that constitute important realities to be observed. The problem that permeates this thesis is the increase in social inequalities in local agriculture, identified in some Brazilian regions, with the allocation of Pronaf resources directed to production chains aimed at the production of agricultural commodities and to more capitalized family farmers, leaving many on the sidelines of this public policy. Given this context, this thesis sought to answer the following question: in practice, is Pronaf truly productivist and selective, as many of the studies presented on this Program point out? It starts from the hypothesis that Pronaf resources have been co-opted for the production of agricultural commodities and used by more capitalized farmers in the two studied cities. This is an explanatory research, with a qualitative approach to the data. The main sources used were legislation, norms and data from Pronaf obtained through the institutional website of the Central Bank of Brazil (Bacen), agricultural censuses from the Brazilian Institute of Geography and Statistics (IBGE), and oral sources produced from direct interviews carried out with Pronaf mediators and family farmers in the region under analysis. The theoretical-methodological framework used is mainly supported by authors such as José D'Assunção Barros, Pierre Bourdieu and Sergio Schneider. These authors approach concepts such as Local History, the different strategies used by social actors, the complexity involved in family farming, the role of the State in agriculture and in the development of public policies for this sector. It was identified as some of the conclusions of the study, that Pronaf has important adhesion in the municipalities of Panambi and Passo Fundo, with a strong concentration of resources in the most capitalized group of family agriculture and with resources directed mainly to the agricultural costing modality, and focused on soybean cultivation. The main articulators are rural extension workers, presidents of Rural Workers Unions and financial institutions at the local level. Pronaf is perceived by local social actors as an important instrument that provides opportunities for family farmers to make investments, however, the increase in interest rates, the income limit for inclusion in the Program and the practice of tied sales by financial institutions are highlighted as limitations of the Program in both municipalities.